Disadvantaged youth report less negative emotion to minor stressors when with peers: An experience sampling study. (January 2017) - Uink, Bep Norma; Modecki, Kathryn Lynn; Barber, Bonnie L.
Previous Experience Sampling Method (ESM) studies demonstrate that adolescents' daily emotional states are heavily influenced by their immediate social context. However, despite adolescence being a risk period for exposure to daily stressors, research has yet to examine the influence of peers on adolescents' emotional responses to stressors encountered in their daily life. Adolescents ( N = 108) from a low-SES school completed ESM reports of their social context, minor stressors and emotions, 5 times a day for 7 days. Based on previous findings that the peer context is experienced as positive and rewarding, we expected being with peers would be associated with lower post-stress negative emotions and higher happiness, compared to being with family or alone. As expected, being with peers after a stressor was associated with lower sadness, worry and jealousy compared to being alone, and lower sadness compared to being with family. Gender differences emerged for the influence of peers on sadness, worry, jealousy and happiness. These findings highlight the salient influence of peers on adolescents' emotional reactivity to stressors as they occur in their natural environment. Findings are discussed in reference to peers as important emotion socialization agents during adolescence and in terms of theories of coping and emotion regulation.